Mechanical Booster Pump-Assisted Thermochemical Mode for Low-Grade Heat Storage and Upgrading: A Thermodynamic Study - Zeng, Tao; Li, Jun; Deng, Lisheng; He, Zhaohong; Kobayashi, Noriyuki; Wu, Rongjun; Huang, Hongyu (Frontiers in Energy Research, 2022)
To assure stable and dependable functioning of the thermochemical energy storage (TCES) system under unstable low-grade heat temperatures, three mechanical booster pump-assisted TCES (MBP-assisted TCES) modes operating with SrBr2·H2O/H2O, LiOH/H2O, and CaCl2·H2O/H2O are proposed for the application of heat storage and upgrading. The operating modes are the MBP-assisted charging mode (A mode), MBP-assisted discharging mode (B mode), and MBP-assisted charging and discharging mode (C mode). A thermodynamic model is established to evaluate the influences of condensing temperature, compression ratio, MBP isentropic efficiency, and reaction advancement on the heat source temperature and system performance from both energy and exergy perspectives. The results indicate that compared with the other two modes, the B mode is more effective in reducing the heat source temperature and achieving better system performance. Compared to the conventional TCES mode, the proposed modes can operate at lower heat source temperatures that can be minimized by up to 21∼25°C by employing the B mode with a compression ratio of 3.0 at the condensing temperature of 24°C. The B mode with SrBr2·H2O/H2O exhibits the highest energy and exergy efficiencies that the coefficients of performance based on total energy input and electric power consumed (COPtotal and COPelec), and exergy efficiency varies in the range of 0.53∼0.59, 7.4∼19.6, and 0.78∼0.95, respectively. In contrast, CaCl2·H2O/H2O shows the lowest system performance, but a higher heat output temperature can be required. In addition, to maintain the MBP discharge temperature below 180°C, there is a maximum permitted compression ratio that varies depending on the operating modes, operating conditions, and working pairs. The findings of this research can be used as theoretical references and suggestions for selecting MBP-assisted TCES modes, operating conditions, and working pairs for low-grade heat storage and upgrading.